BILANGAN DOMINASI DAN BILANGAN DOMINASI HIPER SEMIGRAF BIPARTIT - Indah Permatasari1 (MATEMATIKA FSM, UNDIP, 2015)
BILANGAN DOMINASI DAN BILANGAN DOMINASI HIPER SEMIGRAF BIPARTIT Indah Permatasari1, Djuwandi2, Robertus Heri S.U3 Jurusan Matematika FSM Universitas DiponegoroJl. Prof. H. Soedarto, S.H. Tembalang Semarang permatassariindah@gmail.comrobertusutomo@yahoo.co.id ABSTRACT. Semigraph is a pair where is a nonempty set whose elements are called vertices of and is a set of ordered n-tuples called edges of . A Semigraph called bipartite semigraph if its vertex set can be partitioned into set such that and are independent sets. A set is a dominating set of if adjacent with . If there is not exist is a dominating set such that is a minimal dominating set of and minimum cardinality of a minimal dominating set is called the domination number of and it is denoted by . A set is a hyper dominating set of if hyper dominated by . If there is not exist is hyper dominating set such that is a minimal hyper dominating set of and minimum cardinality of a minimal hyper dominating set is called the hyper domination number of and it is denoted by . The study in this thesis that and are less than or equal to half of the number of vertices in vertex set . Furthermore, studied application of domination number and hyper domination number for products of selling network in the insurance business.Keywords: semigraph, bipartite semigraph, dominating set, domination number, hyper dominating set, hyper domination number